2008
DOI: 10.1074/jbc.m802134200
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Proton Handling by Carbonic Anhydrase II during H+-Lactate Cotransport via Monocarboxylate Transporter 1

Abstract: Carbonic anhydrase (CA) is a ubiquitous enzyme catalyzing the equilibration of carbon dioxide, protons, and bicarbonate. For several acid/base-coupled membrane carriers it has been shown that the catalytic activity of CA supports transport activity, an interaction coined "transport metabolon." We have reported that CA isoform II (CAII) enhances lactate transport activity of the monocarboxylate transporter isoform I (MCT1) expressed in Xenopus oocytes, which does not require CAII catalytic activity (Becker, H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 53 publications
5
105
0
1
Order By: Relevance
“…For a more comprehensive review on bicarbonate transport metabolons see Refs. 39 -41. Using heterologous protein expression in Xenopus oocytes, we have recently reported that CAII enhances transport activity of MCT1 and MCT4, while leaving transport activity of MCT2 unaffected (42)(43)(44)(45)(46). In contrast to the transport metabolons described so far, this interaction is independent of CAII catalytic activity but is mediated by an intramolecular H ϩ shuttle within the enzyme (47,48).…”
mentioning
confidence: 66%
“…For a more comprehensive review on bicarbonate transport metabolons see Refs. 39 -41. Using heterologous protein expression in Xenopus oocytes, we have recently reported that CAII enhances transport activity of MCT1 and MCT4, while leaving transport activity of MCT2 unaffected (42)(43)(44)(45)(46). In contrast to the transport metabolons described so far, this interaction is independent of CAII catalytic activity but is mediated by an intramolecular H ϩ shuttle within the enzyme (47,48).…”
mentioning
confidence: 66%
“…Since most cells express several isoforms of CA, some intra-and some extracellularly (2,22,23), we chose Xenopus oocytes, which are virtually free of any CA activity (17)(18)(19) to test whether intracellular activity mediated by CA IV could be identified in injected oocytes. We observed that oocytes injected with full-length human CA (hCA) IV-cRNA responded with a fast rise of cytosolic H + (H + i ) upon exposure to CO 2 / HCO 3 − -buffered saline, which was inhibited by ethoxzolamide (EZA) in a concentration-dependent manner ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have studied the expression and function of CA IV in injected Xenopus oocytes, which are particularly suited as a heterologous expression system for studying CAs, because they virtually express no intrinsic CA themselves (17)(18)(19). In addition, evidence about the catalytic activity of CA in oocytes, either expressed or injected as protein, can be obtained physiologically by measuring intracellular H + in intact oocytes, and by mass spectrometry of lysed oocytes (20,21).…”
mentioning
confidence: 99%
“…Red blood cells produce lactic acid as a byproduct of the regeneration of ATP during anaerobic glycolysis but cannot use lactic acid. Nguyen and Bonano, [15] [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Carbonic anhydrase facilitate H + in conjunction with lactate removal through monocarboxylate transporters (MCT), which allows continued glycolytic ATP production and thus contributes to pH regulation. It has been reported that MCT dependent lactate-H -flux is facilitated by bicarbonate transporters and carbonic anhydrase (CA) activity in various cells and tissues [4][5][6][7]. It has been reported that inhibition of Carbonic anhydrase was found to impair proton secretion into the proximal tubule lumen.…”
Section: Introductionmentioning
confidence: 99%